Gelatinous transformation of bone marrow: a rare cause of pancytopenia - Dikondwar, Aparna Raghunathrao; Gupta, Anupama Pravin; Kawthalkar, S M; Kumbhalkar, D T; Raut, W K (Annals of Pathology and Laboratory Medicine, 2015)
Gelatinous marrow transformation (GMT) also known as serous atrophy is a very rare entity characterized by fat cell atrophy, accumulation of extracellular gelatinous material in the bone marrow and adjacent marrow hypoplasia. This morphologically defined condition is non specific and can be seen in many hematological and non hematological conditions. Hence, appropriate identification and management of underlying etiology is important. Mostly seen in adult patients and very few cases are reported in pediatric age group. We describe two cases of pediatric age group who presented with pancytopenia. First was a case of protein energy malnutrition and underlying chronic liver disease. Second was a case of disseminated tuberculosis. On bone marrow aspiration both showed fat cell atrophy, marrow hypoplasia and accumulation of extracellular eosinophilic material which was PAS positive suggestive of gelatinous transformation of bone marrow. Our case report adds to the existing literature on gelatinous marrow transformation diagnosed on bone marrow aspiration study. It also suggests that this condition should be looked for as a cause of pancytopenia.